2018
DOI: 10.1088/2058-6272/aae369
|View full text |Cite
|
Sign up to set email alerts
|

High-power microwave propagation properties in the argon plasma array

Abstract: The argon plasma induced by the L-/C-band high-power microwave (HPM) is investigated theoretically and experimentally. Influences of the microwave power, pulse width, polarization and the plasma electron density on the protection performance of the plasma array against HPM are studied. The results show that the effect of HPM is caused by energy accumulation, with the gas breakdown emerging only after a short time. The attenuation of the wave by the plasma array with the tubes off can reach approximately 23 dB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Han et al [3]studied the reflection, absorption and transmission of waveguide plasma limiter. Liu et al [4] studied the characteristics of the interaction between L-band HPM and Ar plasma theoretically and experimentally. The results showed that HPM attenuation of the plasma array is about 23 dB for the L-band.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [3]studied the reflection, absorption and transmission of waveguide plasma limiter. Liu et al [4] studied the characteristics of the interaction between L-band HPM and Ar plasma theoretically and experimentally. The results showed that HPM attenuation of the plasma array is about 23 dB for the L-band.…”
Section: Introductionmentioning
confidence: 99%
“…Low-pressure Mercury vapor discharge plasma has the advantages of low power consumption, large amount of generated plasma, long-term stable maintenance, mature technology, and low cost. Further, such plasma has been widely used in research focusing on the interaction between plasma and electromagnetic waves [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in studies on the interaction between low-pressure Mercury vapor discharge plasma tubes and electromagnetic waves, plasma structure forms include one-dimensional (1D) [17][18][19][20][21][22][23] and two-dimensional (2D) plasma tube arrays [24][25][26]. The main factor investigated is discharge current (power) [21,22,[24][25][26]; changing the discharge current can regulate the effect of the plasma on the electromagnetic wave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas breakdown driven by high-power microwaves has been studied extensively because of its applications in highpower microwave systems, material processing, rocket propulsion, medical treatment, and so on [1][2][3][4][5][6][7][8][9][10][11]. Gas breakdown by microwave in the millimeter regime was paid more and more attention in recent years, due to the development of high-power millimeter wave radiation sources [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%